Influence of Water and Temperature on Ionomer in Catalytic Layers and Membranes of Fuel Cells and Electrolyzers Evaluated by AFM1. Issue 3 (6th March 2018) - Morawietz, T.; Handl, M.; Oldani, C.; Friedrich, K. A.; Hiesgen, R.
Abstract: The major difference for the durability of the materials in PEM fuel cells and PEM electrolyzers is the exposure to humidified gases and to liquid water, respectively. Aquivion and Nafion ionomer was investigated at surfaces of membranes and cross‐sections of electrodes by material‐sensitive atomic force microscopy. The dimensional behavior of electrodes and membranes in a membrane‐electrode assembly cross section was studied as a function of combined humidity and temperature changes. The observed opposite effects of ionomer dimensional changes in membrane and catalytic layers are important for understanding mechanical stress factors and degradation. For the lamellar polymer phase at moderate humidity, a linear swelling behavior and the enclosure of multiples of 0.8 nm‐thick water layers was observed. Submersed in water, 3 nm‐thick enclosed water layers were found. At the water‐immersed Aquivion membrane derived from alcoholic dispersion larger 30–50 nm sized water‐rich areas were found. In contrast, for membranes derived from water‐based dispersion the water‐rich phase was smaller with 11 nm. The thickness of the ultrathin ionomer layers in the electrode was investigated as a function of humidity and temperature. A linear swelling was found for humidity changes whereas nonlinear behavior with 100% expansion and hysteresis was seen for temperature cycles.